Wages and Profits - Marshall, Alfred (Quarterly Journal of Economics, 1888)
Wages and Profits Get access Alfred Marshall Alfred Marshall Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 2, January 1888, Pages 218–223, https://doi.org/10.2307/1879490 Published: 01 January 1888